The Call of Albion : Protestants, Jesuits, and British Literature in Poland-Lithuania, 1567-1775 - Hanusiewicz-Lavallee, Mirosława, (Early Modern History and Modern History E-Books Online, Collection 2024., 2024)
An in-depth look at British-Polish literary pre-Enlightenment contacts, The Call of Albion explores how the reverberations of British religious upheavals in distant Poland-Lithuania surprisingly served to strengthen the impact of English, Scottish, and Welsh works on Polish literature. The book argues that Jesuits played a key role in that process. The book provides an insightful account of how the transmission, translation, and recontextualization of key publications by British Protestants and Catholics served Calvinist and Jesuit agendas, while occasionally bypassing barriers between confessionally defined textual communities and inspiring Polish-Lithuanian political thought, as well as literary tastes.